Effect of Enzymatic Modification Period on Pasting Properties and Functional of Two Varieties of Acha Starch (Digitaria Iburua and Digitaria Exilis) - Olaleye, H. T; Oresanya, T. O.; Akinwande, F. F (European Journal of Applied Sciences, 2023)
Native starches are starches in their pure original form and may not be suitable for many food applications. The use of enzymes to modify starch results in development of low molecular weight, linear short chains fractions of amylopectin, increases the quantity of resistant starch content and promotes freeze thaw stability because amylopectin branches prevent syneresis in the gel network. The effects of enzymatic modification period on the pasting and functional properties of the two Varieties of Acha (Digitaria exilis and Digitaria Iburua) starch were investigated. Acha grains were modified with Enzymes for 30mins, 45mins and 60 mins and non modified Acha grains served as control. The modified starches were evaluated for pasting and functional properties using standard procedure. Results obtained shows: Peak viscosity (2760.00-3752.00RVU), Trough viscosity (1717.00-2888.00RVU), breakdown (713.00-1881.00RVU), final viscosity (2910.00- 4399.00 RVU), setback viscosity ( 1074.00-1652.50), peak time (4.77-6.10mins), pasting temperature (78.28-80.70°c); water absorption capacity (2.03-2.28g/cm3), oil absorption capacity (2.24-8.20g/cm3), bulk density (0.81-4653%), solubility index (1.00-4.12%), swelling power (5.11- 11.50g/cm3) respectively. Enzymatic modification of the two Varieties of Acha grains enhances its functional and pasting properties of Acha based foods.